PENINGKATAN KETRAMPILAN PEMBUATAN ABON IKAN LAYANG (Decapterus sp) UNTUK PEREMPUAN SEKTOR II JEMAAT GPM SILO - Setha, Beni; Loppies, Cindy Regina Magdalena; Soukotta, Dwight; Nendissa, Desire M; Lokollo, Edir (Pattimura University, 2023)
Shredded fish processing is an alternative diversification of fishery product processing which has nutritional value and has a long shelf-life so that it can be stored for a long time at room temperature. Scad fish is an important economical fish, abundant and can be found at any time in the market. Scad fish also has a relatively high nutritional value and is processed at the household level, only fried, grilled and cooked in gravy according to the processing habits of the Maluku people. Processing Scad fish into shredded for sector II women of the GPM Silo congregation is one of the efforts to diversify processed fishery products that have nutritional value and increase knowledge and skills in fish processing which will later increase the income source for women.